Pengaruh Adopsi Financial Technology Terhadap Profitabilitas Bank Umum Konvensional yang Terdaftar di Otoritas Jasa Keuangan Periode 2017-2022 - Yulastri, Yuliana Dwi; Negara, Iwan Kusuma (Postgraduate, University of Mataram, 2024)
This research aims to analyse the effect of financial technology (fintech) adoption on the profitability of conventional commercial banks registered with the Financial Services Authority for the period 2017-2022. This research is an associative research with a quantitative approach. The data collection method is a survey sample. The population in the study amounted to 93 banks. By using purposive sampling technique, 5 bank samples were obtained (30 observation data). Fintech services in this study are measured using Automated Teller Machine (ATM), internet banking and mobile banking. While profitability is measured using Return On Asset (ROA). The panel data analysis method in this research is multiple linear regression analysis using Eviews version 12. The results of this research indicate that Automated Teller Machine (ATM) has a positive and insignificant effect on ROA, internet banking has a negative and insignificant effect on ROA and mobile banking has a positive and significant effect on ROA.